Impact of the underlying cause and co-morbid conditions on the outcome of hepatic encephalopathy - Abdelraheem, Ahmed H.; Elhussein, Amar B.; Magzoub, Aamir A.; Babikr, Walid G. (International Journal of Research in Medical Sciences, 2017)
Background: Hepatic encephalopathy (HE) is a serious neuropsychiatric complication of acute and chronic liver diseases. This study aimed at identifying liver diseases and co-morbidity conditions associated with hepatic encephalopathy (HE) and their impact on patient`s mortality (the outcome). Methods: A hospital-based, prospective study enrolled 76 patients admitted with HE conducted at Ibn Sina specialized gastroenterology hospital, Sudan, from January 2010 to May 2011. Personal data, clinical presentation, underlying liver disease, precipitants, co-morbid conditions and the outcome of HE were obtained from the inpatients’ hospital records. Results: A total of 76 patients were included, 62 males (81.5%) and 14 females (18.5%) aged between 13 and 84 years old. Hepatitis B virus (HBV) was the most common cause of the liver disease (36.8%), followed by HCV (11.8%). Clinically, 53 patients (69%) had impaired level of consciousness. Infection was the most common risk factor for HE (54%) followed by electrolyte disturbance (42%). Overall mortality within one to three weeks following the admission was (50%). The higher percentage of mortality was seen inpatients with late stage autoimmune hepatitis, followed by HCC and in co-morbid conditions like renal impairment (58.8%). Conclusion: HE is associated with a high mortality despite proper management in specialized hospitals. The mortality tends to increase in the presence of comorbid condition.